2019
DOI: 10.18203/2349-2902.isj20192974
|View full text |Cite
|
Sign up to set email alerts
|

Mixer grinder finger tip injuries and treatment outcome in a rural based tertiary center: a retrospective study

Abstract: Background: Early morning mixer grinder fingertip injuries is encountered predominantly in females. Most of these injuries happened due to improper use of the grinder like keeping hands into the mixer when still the blades on run immediately after switching off the machine and sometimes during washing the jar. It can lead to injury of either single or multiple finger and either at single or multiple levels. Early wound debridement and reconstruction is essential for good functional outcome, prevention of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…In our study, 71% of the injuries occurred at the work place while only [8,9]. However, Hongaiah D et al reported female predominance (75%) in their study on fingertip injuries due to mixer-grinders [10]. In their study, the majority of the patients were housewives, who had sustained the injuries while working in the kitchen.…”
Section: Discussioncontrasting
confidence: 50%
“…In our study, 71% of the injuries occurred at the work place while only [8,9]. However, Hongaiah D et al reported female predominance (75%) in their study on fingertip injuries due to mixer-grinders [10]. In their study, the majority of the patients were housewives, who had sustained the injuries while working in the kitchen.…”
Section: Discussioncontrasting
confidence: 50%
“…In our hospital, the department of plastic surgery witnessed a sudden increase in finger/hand injuries due to mixer grinder during the nationwide lockdown. [5,6] Case records of all upper limb injuries including hand injuries in the lockdown period from March 25, 2020, to May 17, 2020, a period of 54 days were examined. There were a total of 32 cases of hand injuries due to mixer grinder, 7 cases of self-inflicted and intended wounds on upper limb, 4 door closing injuries of the hand, 2 cases of scald burns to hand, and 2 cases of upper limb injuries sustained accidentally at home.…”
Section: Methodsmentioning
confidence: 99%
“…In our hospital, the department of plastic surgery witnessed a sudden increase in finger/hand injuries due to mixer grinder during the nationwide lockdown. [ 5 , 6 ]…”
Section: Methodsmentioning
confidence: 99%
“…We reiterate the importance of employees taking every possible preventative safety measure in dealing with machinery equipment. Hongaiah et al discussed in their case study on 12 patients that the most common cause for grinding machine injuries was the usage of the machine without going through the operative manual and accidental injury when machine operators put their hands in the running machine [10].…”
Section: B C 7amentioning
confidence: 99%